2015
DOI: 10.1073/pnas.1520426112
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium evasion of mosquito immunity and global malaria transmission: The lock-and-key theory

Abstract: Plasmodium falciparum malaria originated in Africa and became global as humans migrated to other continents. During this journey, parasites encountered new mosquito species, some of them evolutionarily distant from African vectors. We have previously shown that the Pfs47 protein allows the parasite to evade the mosquito immune system of Anopheles gambiae mosquitoes. Here, we investigated the role of Pfs47-mediated immune evasion in the adaptation of P. falciparum to evolutionarily distant mosquito species. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
167
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(183 citation statements)
references
References 41 publications
16
167
0
Order By: Relevance
“…Sequence analysis of Pfs47 from many different isolates collected around the world indicates that although the predicted proteins have very high protein sequence identity (approximately 99%), multiple haplotypes are present (55). Furthermore, analysis of the geographic distribution of Pfs47 has revealed striking differences between continents (55), in agreement with previous reports (2,51).…”
Section: Plasmodium Immune Evasion and The Globalization Of Plasmodiusupporting
confidence: 82%
See 3 more Smart Citations
“…Sequence analysis of Pfs47 from many different isolates collected around the world indicates that although the predicted proteins have very high protein sequence identity (approximately 99%), multiple haplotypes are present (55). Furthermore, analysis of the geographic distribution of Pfs47 has revealed striking differences between continents (55), in agreement with previous reports (2,51).…”
Section: Plasmodium Immune Evasion and The Globalization Of Plasmodiusupporting
confidence: 82%
“…This study showed that mosquito vectors from Africa (A. gambiae), Asia (Anopheles dirus), and the Americas (A. albimanus) are highly susceptible to infection by P. falciparum isolates from the same region, but they suffer limited infection by isolates from a different continent. The study also indicated that the differences in compatibility are determined by the mosquito immune system (55). These findings raise the question of why different mosquito species are susceptible to infection with different parasite lines.…”
Section: Plasmodium Immune Evasion and The Globalization Of Plasmodiumentioning
confidence: 74%
See 2 more Smart Citations
“…albimanus, are selecting the P. vivax populations circulating in the highlands and coastal areas in southern Mexico, respectively (13). Moreover, recent studies indicate that the immune system of some anopheline mosquito species can select the P. falciparum parasites circulating in a given geographic region (14).…”
mentioning
confidence: 99%